Resting coronary blood flow velocity profile predicts coronary flow reserve in HFpEF. (25th November 2020) - Svedlund, S; Brodin, T; Hage, C; Saraste, A; Tan, R.S; Beussink-Nelson, L; Faxen, U.L; Lagerstrom Fermer, M; Lam, C.S.P; Shah, S.J; Lund, L; Gan, L.M
Abstract: Background: Coronary microvascular disease (CMD) is prevalent in patients with heart failure with preserved ejection fraction (HFpEF). CMD can be assessed by coronary flow reserve (CFR) using transthoracic echocardiography (TTE). We hypothesised that the coronary Doppler flow profile in LAD at rest could reveal information about the downstream resistance in the vessel, where increased resistance is a sign of CMD. Purpose: We aimed to measure features of the acceleration and deceleration of the LAD Doppler flow profile to investigate association with coronary and cardiac function. Methods: CFR was assessed in 202 patients by TTE in the PROMIS-HFpEF-study. Detailed flow profile measurements were possible in 169 patients (84%) who constituted the study population. The coronary Doppler flow profiles were analysed with respect to acceleration time (corAT) and slope (corAS) and deceleration pressure half time (corPHT) (figure 1). Results: The average age was 75±9 years and 55% were female. Atrial fibrillation (AF) was present in 53% and 62% were current or previous smokers. There was no significant difference in gender, age, BMI, blood pressure or heart rate in the CMD vs non-CMD group, but AF as well as a history of smoking was more prevalent in the CMD group, p=0.022 and 0.003 respectively. Further, there were no significant differences in neither corAT nor corAS between the two groups. However, patients with CMD had shorter corPHT of 268±64 ms compared to 298±67 ms, p=0.01. A longer corPHT was associated with increased TAPSE (R=0.205, p=0.007) and higher CFR (R=0.231, p=0.002). In a multivariable analysis adjusted for age, sex, BMI, SBP, reactive hyperemia index, HR, AF, diabetes, CVD, smoking, LVM and study site*, corPHT independently predicted CFR (table 1, p=0.016). Conclusion: Short pressure half time, indicating a steep deceleration of the coronary Doppler signal at rest, may provide useful information for prediction of CFR determined by transthoracic ultrasound by reflecting the increased resistance in the coronary microvasculature associated with CMD. Funding Acknowledgement: Type of funding source: Public hospital(s). Main funding source(s): Sahlgrenska University Hospital, Sponsor AstraZeneca